(untitled) (UNIZIK Journal of Educational Management and Policy, 2025)
The purpose of the study was to ascertain relationship between the perceived use of artificial intelligence driven tools and perceived administrative effectiveness in public secondary schools in Anambra State. Correlation research design was used for the study. The population of the study consisted of 268 public secondary school principals in Anambra State. No sampling technique was done as the population is of manageable size. Data for the study were obtained collected using two sets of questionnaire. Data were analyzed using Pearson Product Moment Correlation coefficient. The findings of the study revealed that a high positive and significant relationship existed between principals’ perceived use of AI-powered analytics and perceived administrative effectiveness in public secondary schools. Based on the findings of the study, it was recommended among others that Ministry of Education should organize seminars and workshops for principals on the need to improve on their use of AI-driven infrastructure for administrative effectiveness.